Numerical Survey of the Solar Magnetic Field - Beijersten, Caroline (2006)
This MSc diploma thesis in Space Engineering at Luleå University of Technology, was carried out at Monash University in Melbourne, Australia. It is within the area of solar physics with focus on the magnetic field of the Sun. Within solar physics, the process generating the magnetic field of the Sun is normally referred to as the solar dynamo. An important tool when it comes to understanding the magnetic field of the Sun and its interactions with the whole solar system, is to construct solar dynamo models. The aim is to obtain a model, which produces output corresponding to the solar observations and which preferably also could be used to predict the solar magnetic activity. A solar flux transport dynamo model code, which was to be used for the project, was provided by Dr. M. Dikpati. It simulates the magnetic field of the Sun for a half-sphere solution and the output can be compared to solar observations. The initial focus of the project was set on varying a specific magnetic field parameter in the code and the effects the variations would have on the solar dynamo model. Interaction of two different kind of these parameters could possibly lead to destructive interference, which could terminate the solar dynamo or lead to a significant decrease of its magnitude. If such a relation is found, it could possibly be related to the grand minima which has been observed in sunspot occurences. Some additional numerical surveys were also made, plus two subprojects of trying to extend the provided code to a full-sphere solution and to reproduce output for a low-order dynamo model. Considering the main focus of the project, the differences that could be identified for varying the magnetic field parameter, were related to the field strength and locations of the different kind of solar magnetic fields. Regarding some of the flow parameters connected to the magnetic field, some conclusions could be made related to their effect on the solar dynamo. For example, the surface-flow velocity is an efficient parameter for regulating ...